Implementasi Komunikasi Visual dan Digitalisasi UMKM: Studi Kasus Medin Bali Cafe pada Program P2MW 2025 - Ni Putu Sinmby Octaria Putri; Ida Bagus Ardhi Putra (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
The Sanur area, as a tourist destination in Bali, offers significant opportunities for the development of culinary businesses. However, Medin Bali Café still faces challenges in managing visual communication and digital marketing, such as an unstructured social media presence and suboptimal use of digital platforms. This study aims to analyze the implementation of digital mentoring by Gumi Production in improving Medin Bali Café's visual branding and digital marketing. This digital mentoring and restructuring program was carried out intensively for six months during the 2025 Student Entrepreneurship Development (P2MW) grant period, focusing on strategies to optimize social media and improve the partner's operational management. This study employed a descriptive qualitative and quantitative approach through social media audits, interviews, digital content production, multiplatform distribution, and evaluation using the AIDA model. The results showed a significant increase in social media performance, marked by higher Instagram and Facebook impressions, a 59% increase in engagement, and an expansion of new audience reach by 47.8%. Digital mentoring also proved effective in improving the efficiency of operational content management and strengthening Medin Bali Café's visual identity in a professional and consistent manner